TRANSLATING CULTURAL REALITIES: CHALLENGES OF INTEGRATING UZBEK AND ENGLISH WORLDVIEWS - Rashidova Dilnura (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
This article analyzes the challenges of translating culture-specific realities between Uzbek and English languages, emphasizing the need to preserve both linguistic accuracy and cultural authenticity. It explores the relationship between worldview, culture, and translation, arguing that translation is not merely linguistic substitution but cultural mediation. The study also examines examples from literary and media texts, demonstrating strategies for conveying culturally bound meanings effectively.